Pendulum systems for harvesting vibration energy from railroad tracks and sleepers during the passage of a high-speed train: A feasibility evaluation - Dotti, Franco Ezequiel (2019)
We evaluate the feasibility of recovering energy from the passage of a high-speed train, by means of a pendulum harvester. A simple mathematical model of the parametric pendulum is employed to obtain numerical predictions, while measured data of vibration tests during the passage of a Thalys high-speed train are considered as input forcing. Since a sustained rotation is the most energetic motion of a pendulum, the possibility of achieving such state is evaluated, taking into account the influence of initial conditions, damping and other factors. Numerical simulations show that rotating pendulum harvesters with sufficiently low viscous damping could be able to generate a usable average power on the order of 5-6 W per unit. Considering a modular arrangement of devices, such energy is enough to feed variety of rail-side equipment, as wireless sensors or warning light systems. However, a suitable choice of initial conditions could be a difficult task, leading to the need of a control action.